PTH-036 Single Centre Experience of The Use of Needle Knife Papillotomy During Difficult ERCP: Is It Safe and Should It Be Used By, and Taught to Trainees. (17th August 2016) - Rabb, N; Beckett, C; Jowett, S; Moreea, S
Abstract : Introduction: Despite previous concerns regarding the safety of needle knife papillotomy (NKP) there is data to support its efficacy and safety in the context of increasing bile duct cannulation at ERCP. 1 This data predominantly originates from high volume tertiary centres outside the UK. We audited our experiences of using NKP in a secondary care centre where wire-guided cannulation is the standard method for accessing the bile duct and the overall ERCP complication rate is <5%, focusing on success of bile duct cannulation in relation to pathology, safety of the procedure and complication rate. Methods: Electronic databases and medical records were interrogated to retrieve data for analysis on all ERCP cases using NKP between 2010–2015. The following data was collected: patient (pt) demographics, indications for ERCP and subsequent complications. Results: 1843 ERCP were performed on 1362 pts (817 female (F), 545 male (M), age range (AR) 16–103). NKP was performed in 69 cases (3.7% 37F 32 M, AR 21–98). In the papillotomy cohort indications for ERCP were stone disease (40); stricturing disease (22); others including unexplained pancreatitis (4), bile leak (2), sphincter of Oddi dysfunction (1). Successful bile duct cannulation was achieved during the index procedure in 50 cases (25M 25 F). Of the remaining 19 cases, 11 (5M 6 F) had bile duct cannulation achieved during a repeat procedure via the papillotomy: global success rate 88%. The remaining 6 cases (4F 2 M) were managed with alternative interventions (5 PTC, 1 surgical). NKP was more successful for stone disease: an initial procedure success rate of 73% vs. 64% for non-stone disease, increasing to 95% with repeat procedure. 5/6 (83%) cases requiring alternative interventions had non-stone disease. Complications: 4/69 (5.8%) cases were complicated by pancreatitis; all were managed conservatively with no associated mortality. 3/4 (75%) required hospitalisation for <3 days and 1 for >10 days. There were 4 cases of bleeding (5.8%) with 2/4 (50%) requiring blood transfusion and endoscopic therapy to achieve haemostasis. Perforation occurred in 2 cases (2.8%); both were managed conservatively, 1 case died. Conclusion: The global success rate for bile duct cannulation after pre-cut NKP was 88% which supports its efficacy for obtaining bile duct access in otherwise difficult ERCP cases. The overall complication rate of 13% associated with the technique is high, though comparable to other published data. Acknowledgement that NKP may be less fruitful in cases of non-stone related disease may help to guide our practice further, particularly by helping identify cases that may be more appropriate for trainees to tackle. Reference: 1 Baillie J. GIE 79 (5): 2014. Disclosure of Interest: None Declared